Comparison of post-authorisation measures from regulatory authorities with additional evidence requirements from the HTA body in Germany: Are additional data requirements by the Federal Joint Committee justified? - Jörg Ruof; Thomas Staab; Charalabos-Markos Dintsios; Jakob Schröter; Friedrich Wilhelm Schwartz (Health Economics Review, 2016)
Objectives: The aim of this study was to compare post-authorisation measures (PAMs) from the European Medicines Agency (EMA) with data requests in fixed-termed conditional appraisals of early benefit assessments from the German Federal Joint Committee (G-BA). Methods: Medicinal products with completed benefit assessments during an assessment period of 3.5 years were considered. PAMs extracted from European Public Assessment Reports (EPARs) were compared with data requests issued by the G-BA in the context of conditional appraisals. Results: Twenty conditional appraisals (19 products) and 34 EPARs containing PAMs (33 products) were identified. Data categories (efficacy, safety, etc.), data types (type of study required to address the request) and clarity of requests were determined. Conditional appraisals disproportionately focused on oncology products (13/19 products with conditional appraisals vs. 14/33 products with PAMs). No clear rationale for the G-BA issuing conditional appraisals could be identified in public sources. Both EMA and G-BA requested mainly efficacy and safety data (44/54 and 23/35 categories requested, respectively); however, 28/35 G-BA data requirements went beyond requests made by the EMA. Almost half of the G-BA requests (9/20), but no PAMs, were unclear, and no methodological guidance for fulfilling the data requirements was provided by the G-BA. Conclusions: Better alignment between data requests from regulatory authorities and health technology assessment bodies is strongly recommended.
Keywords: 330; Marketing authorisation; Post-authorisation measure; (Early) benefit assessment; Conditional appraisal; EMAG-BA